2007
DOI: 10.1007/s10562-007-9243-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nanowire TiO2 Thin Films by Hydrothermal Treatment and their Photoelectrochemical Properties

Abstract: Nanowire TiO 2 thin films were successfully prepared on Ti metal substrates by hydrothermal treatment of calcined Ti foils in 10 M NaOH. The nanowire TiO 2 thin films exhibited much larger surface area and higher photoelectrochemical performance than the TiO 2 thin films prepared on Ti metal substrates by the calcination of Ti foil. These nanowire films were shown to act as an efficient photoanodes for the photoelectrochemical water splitting reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 29 publications
(34 reference statements)
0
22
0
Order By: Relevance
“…The design of systems involving the heterojunction of these two nanomaterials is an interesting approach since has been already reported in the literature that the synergic effect caused by the combination of metal oxides can improve the photocatalytic activity by lowering the recombination rates 14,15 . For use as photoanodes in photoelectrocatalysis, these materials must be immobilized on a conductive surface, which is a challenge for TiNTs because all of the strategies used for this goal resulted in films in which the nanotubes are randomly orientated and packed in a dense film layer, which can especially affect the electron transport 8,[16][17][18] . For this reason TiNTs have been used mostly as photocatalysts for water splitting in the powder form, as is shown in the upper part of Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…The design of systems involving the heterojunction of these two nanomaterials is an interesting approach since has been already reported in the literature that the synergic effect caused by the combination of metal oxides can improve the photocatalytic activity by lowering the recombination rates 14,15 . For use as photoanodes in photoelectrocatalysis, these materials must be immobilized on a conductive surface, which is a challenge for TiNTs because all of the strategies used for this goal resulted in films in which the nanotubes are randomly orientated and packed in a dense film layer, which can especially affect the electron transport 8,[16][17][18] . For this reason TiNTs have been used mostly as photocatalysts for water splitting in the powder form, as is shown in the upper part of Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yada et al have reported that titanate nanotube films can be formed on Ti substrates by hydrothermal treatment of Ti foils in 10 M NaOH solutions at 160℃ [16,17]. Similar studies on the formation of titanate nanotube films via hydrothermal treatment method have also been reported by a number of other research groups [15,[18][19][20][21][22]. Recently, Hu et al have treated Ti foils in 10 M NaOH solutions at 180℃ in the presence of oxidative organic compounds and found that titanate nanowire films, rather than nanotube films, are formed [21].…”
Section: Introductionmentioning
confidence: 56%
“…15 M) or using a rotating autoclave [9] favors the formation of nanowires. In recent years, the extension of such hydrothermal method to treatment of Ti foils for fabricating titanate nanotube or nanowire films on Ti substrates has also been aroused increasing interest [15][16][17][18][19][20][21][22] because the formed films can be directly used as photoanodes for photocathodic protection for stainless steel [22] or converted to TiO 2 films for water splitting [20] and decomposition of harmful compounds [21]. For example, Yada et al have reported that titanate nanotube films can be formed on Ti substrates by hydrothermal treatment of Ti foils in 10 M NaOH solutions at 160℃ [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…[79] This is an important topic for further studies on size-selective catalysts, which can utilise the geometry of cylindrical pores of 3-8 nm in diameter and avoid the formation of bulky side products. [155] of Cr-TiNT H 2 + O 2 implantation TiO 2 NP (anatase) Calcination H-TiNT n/a n/a Photocatalytic oxiHigher than that Novel route for anatase [140] dation of organics of P25 nanoparticles TiO 2 NR (anatase) Calcination H-TiNT 10ϫ100 nm n/a Photocatalytic oxiHigher than that Novel route for anatase [46,141] dation of organics of P25 nanorods Pt/TiNT Photodeposition n/a 1 wt.-% CH 3 CH 2 OH + hν n/a Early data on photodehy- [165] Ǟ CH 3 CHO + H 2 drogenation CdS/TiNT Ion-exchange sur-6 nm n/a Dye oxidation n/a Photosensitisation of [156,157] face reaction TiNT N-doped TiO 2 [160] of P25 tunnel structure TiO 2 /TiNF Epitaxial growth by 10-50 nm n/a Dye oxidation Higher than that Support for photocatalyst [147] precipitation of TiNF TiO 2 NF, TiO 2 NP Acid treatment of n/a n/a Dye oxidation Comparable with Novel route for [144] TiNF at 180°C that of P25 nanostrucuted anatase Pt/TiNT Sputtering n/a n/a H 2 O + hν Ǟ Higher than that Early data showing water [163] H 2 + O 2 of TiO 2 splitting SnTTP/TiNF…”
Section: Reaction Catalysismentioning
confidence: 89%
“…The photocatalytic oxidation of methyl orange showed a synergistic enhancement of activity under both UV and visible illumination. [161] In conclusion, elongated titanate and TiO 2 nanostructures have been considered for photocatalytic processes including oxidation of organic waste in air and water, [140,141,162] splitting of water [155,163] and generation of hydrogen by using sacrificial hole scavengers [146,164,165] (see Table 4). A comparison of elongated morphologies [164] for hydrogen evolution from methanol indicated that the photocatalytic activity followed the trend: anatase NF Ͼ TiO 2 -(B) NF ϾϾ H-TiNF.…”
Section: Photocatalysis In Elongated Titanatesmentioning
confidence: 99%